2019
DOI: 10.1111/resp.13611
|View full text |Cite
|
Sign up to set email alerts
|

Assessing appropriateness of paediatric asthma management: A population‐based sample survey

Abstract: Background and objective We conducted a comprehensive assessment of guideline adherence in paediatric asthma care, including inpatient and ambulatory services, in Australia. Methods National and international clinical practice guidelines (CPG) relating to asthma in children were searched and 39 medical record audit indicator questions were developed. Retrospective medical record review was conducted across hospital inpatient admissions, emergency department (ED) presentations, general practice (GP) and paediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Care fragmentation and inequity is widespread and has been associated with poor health outcomes 24,25 . End‐users expressed a common desire for researching effective training and educational strategies for improving asthma knowledge among clinicians.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Care fragmentation and inequity is widespread and has been associated with poor health outcomes 24,25 . End‐users expressed a common desire for researching effective training and educational strategies for improving asthma knowledge among clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Care fragmentation and inequity is widespread and has been associated with poor health outcomes. 24,25 End-users F I G U R E 3 Theme frequency by end-users. (A) response to question 1: 'what you would like to see answered by research to improve living with asthma on a day-to-day basis?'…”
Section: Asthma Care and Self-managementmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to improve asthma control among the paediatric age group, a personalized guidance for managing the symptoms, through a written action plan is essential [20].Studies have shown that having a written asthma treatment plan can significantly reduce the number of ER visits due to asthma attacks [21].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent publication in Respirology , Homaira et al . present the detailed guideline adherence in paediatric asthma from the CareTrack Kids study . A total of 39 indicators of quality asthma care were developed from three major asthma clinical practice guidelines.…”
mentioning
confidence: 99%